2022
DOI: 10.1111/aji.13655
|View full text |Cite
|
Sign up to set email alerts
|

Circulating CD200 is increased in the secretory phase of women with endometriosis as is endometrial mRNA, and endometrial stromal cell CD200R1 is increased in spite of reduced mRNA

Abstract: Problem Estrogen‐dependent extrauterine implantation and growth of menstrual endometrial tissue affects roughly 10% of reproductive age women and depends on suppression of local innate immune defenses to prevent ectopic tissue rejection. Immunohistochemistry has shown the immune check‐point inhibitor CD200 which can suppress rejection is expressed in eutopic endometrium and in ectopic deposits. Soluble CD200 accumulated in venules draining eutopic and ectopic endometrium of endometriosis cases in the secretory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Moreover, the level of CD200 in the serum correlated with a matched level of CD200 mRNA in the endometrium. On the other hand, they observed a correlation between a lower level of circulating CD200 and a lower expression of the CD200 mRNA in the secretory phase in the endometrium of the control group [ 69 ]. Abramiuk et al found higher percentages of CD4 + , CD8 + T cells, and CD19 + B cells with CD200 expression in EMS patients when compared to the control group.…”
Section: Other Less Common Icps In Endometriosismentioning
confidence: 99%
“…Moreover, the level of CD200 in the serum correlated with a matched level of CD200 mRNA in the endometrium. On the other hand, they observed a correlation between a lower level of circulating CD200 and a lower expression of the CD200 mRNA in the secretory phase in the endometrium of the control group [ 69 ]. Abramiuk et al found higher percentages of CD4 + , CD8 + T cells, and CD19 + B cells with CD200 expression in EMS patients when compared to the control group.…”
Section: Other Less Common Icps In Endometriosismentioning
confidence: 99%